Marketing and promotion of quality. Geographical designations of origin in seafood products. The case of Spain - Seoánez Calvo C. (Global quality assessment in Mediterranean aquaculture, 2000)
The designations linked to a geographical area (Protected Designation of Origin and Protected Geographical Indication) are analysed and compared with other designations linked to production methods (Generic Designation and Traditional Speciality Guaranteed). Mention is made of other types of designation, promoted mainly by the Autonomous Communities (designations of quality and regional distinctive labels), as well as other possibilities of differentiating identification, such as collective brands and guarantee brands. An analysis is then made of the general adaptation of fish products to the distinctive symbols mentioned, emphasising the difficulties that arise in these products when conditions are applied to them that have been established for agricultural and livestock products.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)